Key Performance Indicators of customer service in SYKES outsourcing company - Sitková, Petra (Univerzita Pardubice, 2010)
This work focus on measurable Key Performance Indicators, their evaluation and concept improvement in outsourcing company SYKES in Budapest. It also deals with forms, types, advantages and risks of outsourcing. The thesis describes particular indicators and suggests possible solutions for result improvement.
Klíčové indikátory výkonu zákaznického servisu outsourcingové firmy SYKES
Keywords: Outsourcing; zákaznický servis; customer support